The Policy on Appointing Former Directors of Bankrupt Companies as Directors of State-Owned Enterprises Viewed from the Principles of Good Corporate Governance - Muhammad Abduh; Atik Winanti; Irwan Triadi (Nusantara: Journal of Law and Islamic Law, 2026)
This research analyzes the legal policy and validity of appointing former directors of bankrupt companies to the boards of State-Owned Enterprises (SOEs) under the principles of Good Corporate Governance (GCG). Utilizing a normative legal research method with statutory and case study approaches, the study specifically examines the appointment of Sigit Winarto as Director of PT JIEP following the bankruptcy of PT Istaka Karya. The findings demonstrate that such an appointment explicitly violates Article 93 of the Company Law in conjunction with Article 15 of the SOE Law, as it transpired within the mandatory five-year prohibition period without valid judicial rehabilitation. Consequently, the appointment is void ab initio due to substantive legal defects and contravenes the GCG principles of responsibility and accountability. Therefore, rigorous enforcement of administrative sanctions against the appointing authorities is imperative to safeguard the integrity of state asset management and to ensure legal certainty and public trust in the professionalism of SOE governance in Indonesia.